Treatment of generalized spacing with clear aligner therapy: Report of a case - Kafle, Dashrath; Mahato, Ravi Kumar; Giri, Abhisek; Luintel, Sanjiv; Karki, Arjun (Orthodontic Journal of Nepal, 2021)
Clear Aligners are becoming popular among patients in recent years because of its invisible nature , comfort to wear, less orthodontic emergencies and better hygiene control. However proper case selection is vital for the success. With the better understanding of aligner biomechanics and improvement in aligner materials and attachment design, more complex teeth movement is also possible with clear aligners. As there is always controversy on whether aligners cause tipping or bodily tooth movement, In this case report, a skeletal class I patient with generalized spacing in maxilla and mandible is presented which is treated effectively by bodily movement of incisors.